Michael Symons: One Continuous Picnic - Cookson, Caroline (Petits Propos Culinaires, 2024)
Michael Symons: One Continuous Picnic: Duck Press, Adelaide, 1982: 278 pp., hardback, black and white illustrations, distributed in Europe and North America by Prospect Books, £13.00, US 22.50.